(untitled) (Research, Society and Development, 2020)
With the economic and population growth of certain nations, the need for energy sources has increased, and the fact that the world is dependent on fossil fuels is quite worrying, since they have finite and potentially polluting characteristics. These conditions encourage the growing search for renewable and “clean” sources to help supply the world’s energy demand. Thus, many studies focus on the processes of converting agro-industrial waste, a big challenge in the proper destination when considering the huge amount of debris generated. Among these processes, thermochemical conversion through pyrolysis stands out. In order to perform the statistical survey through the bibliometric approach about the pyrolysis of banana residues, this work was built through Scopus and Web of Science databases, focusing on the use of these residues as biomass for energy generation. As a result, the notable growth of studies over the years regarding the use of pyrolysis as a waste conversion process was evidenced. It was concluded that the potential use of banana crop residues as biomass for production of alternative energy sources is highlighted in research conducted in countries that are considered the world’s largest fruit producers.